PENGARUH KEPEMIMPINAN DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN BIDANG EKONOMI YAYASAN WAKAF ARRISALAH - Arwin Tanjung; Febsri Susanti (Jurnal Bina Bangsa Ekonomika, 2022)
Organizational performance is the end result of the work done to achieve predetermined organizational goals. Employee performance can be improved by providing a good example of a leader, motivating employees and always pay attention to employees in the work. Leadership is an activity to influence the behavior of others so that they would be directed to achieve certain goals. Employee motivation is a response to a number of statements about the overall business arising from within the employees to drive to work and grow the desired goal can be achieved. This study aims to analyze the influence of leadership and work motivation on employee performance at the economics of the arrisalah waqf foundation. Population in this study were 70 employees who is also a sample of the entire population at the economics of the arrisalah waqf foundation. Studies using multiple regression analysis. The results of this study indicate leadership have a positive and significant effect on employee performance. Work motivation have no significant impact on employee performance